Effects of Various Fertilizers and Different Nitrogen Doses on Pumpkin Seed and Plant Water Consumption. Issue 5 (9th March 2022) - Ünlükara, Ali; Varol, İhsan Serkan; Güneş, Adem
ABSTRACT: This experiment was conducted to investigate the effects of different fertilizer and nitrogen doses on pumpkin seeds at the Erciyes University Agricultural Research and Application Center during the years 2017 and 2018. In this study, three different fertilizer types were tested as compost + mineral fertilizer (K + M), organo-mineral fertilizer (OM), and mineral fertilizer with different nitrogen doses at 90, 120, and 140 kg ha −1 (N1, N2, and N3 ). The experiment, which used the Develi pumpkin seeds, was carried out in a randomized block design. The organic fertilizer significantly increased the average fruit weight and yield. The fruit yield was 37.31, 36.44, and 32.68 t ha −1 with the use of K + M, OM, and M, respectively. The number of fruits per plant, seed yield, and 1000 grain weight is not affected by the fertilizer types or nitrogen doses. For the two-year average, seed yield was obtained 907, 949, and 863 kg ha −1 from K + M, OM, M, and 904, 937, and 878 kg ha −1 from N90, N120, and N140, respectively. Compost and organo-mineral fertilizer applications significantly affected the fruit and seed yield. More stable results were obtained by the application of compost fertilizer and 120 kg ha −1 nitrogen dose every 2 years. Increasing the soil organic matter and applying 120 kg ha −1 nitrogen dose in pumpkin seed agriculture would be useful.